Implementation of a Structured Inquiry Learning Model Based on the Local Wisdom of to Improve Students' Critical Thinking Skills on the Material of Work and Energy - Najwan Naufah; Beni Setiawan; Mohammad Romadhoni (Universitas Syiah Kuala, 2026)
Students' mastery of physics can be improved through local wisdom-based learning. One of these is the use of the traditional game of Egrang. Therefore, this study aims to describe the improvement of students' critical thinking skills (CTS), learning implementation, and student responses after the application of the structured inquiry learning model based on local wisdom of the Egrang game on the material of work and energy. The method used is quantitative descriptive. The research sample was selected using a purposive sampling technique, namely 25 students of class VIII-A MTsN 2 Lamongan. The instruments used were pretest and posttest questions, learning implementation observation sheets, and student response questionnaires integrated with structured inquiry syntax and 3 indicators CTS consisting of interpretation, evaluation, and self-regulation. The results of the study showed an increase with an N-gain score of 0.54 in the moderate category. The results of the Shapiro-Wilk normality test had a significance value > 0.05, indicating that both data sets met the assumption of normality. Meanwhile, the paired t-test analysis revealed a significant increase with a p-value <0.001 based on a 95% confidence interval. These results are supported by the results of learning implementation and student responses. Learning implementation in the first meeting reached an average percentage of 92.97% and in the second meeting reached an average percentage of 98.04%, so both were included in the very good category. Meanwhile, student responses reached an average percentage of 89.7%, which is categorized as very strong. Therefore, it is believed to be a potential long-term educational investment. However, to realize this, optimal strategies are needed, including teacher training, learning facilities, and curriculum adjustments